The effects of Project Approach Based Education Program on creative thinking of children - Akyol, Tugce; Can Yaşar, Münevver (Southeast Asia Early Childhood Journal, 2022)
The aim of this study is to evaluate the effects of the Project Approach Based Education Program on the creative thinking skills of 61-66 month old children. A pretest, posttest, retention test experimental design with control group was adopted in the study. The study group comprised a total of 44 children, 22 of them assigned to experimental group and 22 to the control group. As the data collection tools, the “Personal Information Form” and “The Test for Creative Thinking-Drawing Production (TCT-DP)” was used, which was originally developed by Urban and Jellen (1996) and adapted to Turkish children by Can Yaşar and Aral (2011a) in order to evaluate the creative thinking skills of children. Project Approach Based Education Program which aimed to support children’s creative thinking skills was implemented three days a week for 10 weeks. While analyzing the data, Mann Whitney U Test for the difference between groups and Wilcoxon Signed Rank Test and Friedman’s Two-Way ANOVA tests for comparison within groups were used. At the end of the study, it was found that there was statistically significant difference between the pre-test score averages and post-test/retention test score averages concerning the Form A, Form B, and total (A+B) of TCT-DP of the children in the experimental group participating in the project-approach based education program. It was determined that there was a significant difference among the Form A, Form B, and total (A+B) post-test score averages of the children in the experimental and control groups.